2019
DOI: 10.1038/s41598-019-51157-1
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oncogenic, intra host viral quasispecies in Diffuse large B cell lymphoma patients with occult Hepatitis B Virus infection

Abstract: Non Hodgkin lymphoma, predominantly Diffuse Large B-cell Lymphoma (DLBCL) has been reported to have a significant association with Hepatitis B virus (HBV). We investigated the presence of different gene segments of HBV in plasma, B-cells and tumor tissues from DLBCL patients and explored the genetic variability of HBV within and across different compartments in a host using Next Generation Sequencing. Despite all 40 patients being HBV seronegative, 68% showed evidence of occult HBV. Sequencing of these gene se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Next generation sequencing revealed the presence of genetic variants associated with increased HCC risk A1762T/G1764A in both the PBMC and DCS tumor [ 127 ]. Similarly, in a study of 40 HBV seronegative DLBCL patients, Sinha et al identified occult HBV infection within 27 (67.5%) cases [ 140 ]. Furthermore, they reported the detection of HCC-associated HBV genetic variants such as X/BCP/PC and surface mutations within plasma, B-cells, and tumor tissues.…”
Section: Unique Features Of Hbv That Impact Treatment and Oncogenementioning
confidence: 99%
“…Next generation sequencing revealed the presence of genetic variants associated with increased HCC risk A1762T/G1764A in both the PBMC and DCS tumor [ 127 ]. Similarly, in a study of 40 HBV seronegative DLBCL patients, Sinha et al identified occult HBV infection within 27 (67.5%) cases [ 140 ]. Furthermore, they reported the detection of HCC-associated HBV genetic variants such as X/BCP/PC and surface mutations within plasma, B-cells, and tumor tissues.…”
Section: Unique Features Of Hbv That Impact Treatment and Oncogenementioning
confidence: 99%
“…Although hepatitis B virus (HBV) is an essentially hepatotropic DNA virus, it also exhibits the capacity to infect peripheral blood mononuclear cells, including non-Hodgkin lymphoma (NHL) cells. 1,2 Besides being a risk factor for developing hepatocellular carcinoma, epidemiologic studies have suggested that chronic HBV infection can increase the risk of B-cell NHL, and it has been endorsed in a recent meta-analysis showing that HBV infection is significantly associated with diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL). 3 Patients with occult HBV infection (presence of HBV DNA in liver and/or serum, with undetectable hepatitis B surface antigen [HBsAg]) and resolved HBV infection (HBsAg − and anti-HBcore + [anti-HBc + ]) have been shown to contribute to the risk of developing NHL, although these situations are not considered in some studies because of the inadequacy of such information.…”
Section: Introductionmentioning
confidence: 99%
“…This study pointed out the importance of thorough analysis of immune cells from HBV-infected patients for the presence of virus and its integration. This study provides further invaluable insights to recognition of the relationship between HBV and immune system malignancies and suspected virusoncogenic potential (Engels et al, 2010;Li et al, 2018;Ren et al, 2018;Sinha et al, 2019).…”
Section: Hepadnavirus Integration Into Immune Cell and Lymphatic Organ Genomesmentioning
confidence: 90%
“…Furthermore, next generation sequencing of HBV-infected PBMC from CHB patients showed the presence of genetic variants associated with enhanced risk of HCC development (i.e., A1762T/G1764A) (Lau et al, 2020). In another study, OBI was identified in the majority (67.5%) of patients with diffuse large B cell lymphoma and HCCassociated HBV variants were identified in plasma, PBMC and lymphoid tumor tissue of these patients (Sinha et al, 2019). These data overall support the longstanding concept regarding the oncogenic role of HBV lymphotropism in the pathogenesis of immune cell malignancies.…”
Section: Hbv Integrationmentioning
confidence: 95%